Delayed Cerebral Metastasis of Breast Cancer: Case Report and Molecular Review - Olijnyk, Leonardo Dessesards; Morais, Artur Nobrega Lima; Carvalho, Rodolfo Figueiredo; Abrão, Adriana; Patel, Krunal; Silva, Carlos Eduardo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Breast cancer (BC) is a prevalent disease, and its incidence of brain metastasis (BM) varies from 5 to 30% according to the literature. We present the case of a delayed isolated cerebral metastasis in a female patient following a period of 16 years after the diagnosis and first treatment. During this time, there was no other recurrence. We also review the literature concerning central nervous system spread and the molecular subtypes of such late tumors.
Keywords: breast cancer; neuro-oncology; delayed metastasis